Olive leaf extract as a crosslinking agent for the preparation of electrospun zein fibers. Issue 4 (28th August 2014) - Erdogan, Ipek; Demir, Merve; Bayraktar, Oguz
ABSTRACT Incorporating active agents, reinforcing structure by crosslinking, thus changing release properties, can be listed as possible modifications in preparation methods of biopolymer fibers. This study introduces oleuropein, major component of olive leaf extract (OLE), as a natural functional crosslinker for electrospun zein fibers, owing to its antioxidant and antimicrobial properties. Incorporation of OLE causes morphological and structural changes indicated by a decrease in fiber diameter up to 27%, an increase in intensity of NH bending region due to interaction with –OH groups and observation of characteristic oleuropein bands. Extract addition also enhances thermal stability. Zein fibers without OLE is fully degraded at 600°C, whereas 10% of OLE loaded zein fibers is left undegraded. Fifty percent of initial phenolic content loaded into fibers is released which indicate the effect of OLE incorporation as accumulation of oleuropein. OLE‐incorporated fibers immersed in PBS are less fused than pure zein fibers, due to the crosslinking effect. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41338.